2021
DOI: 10.3389/fphar.2021.694375
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Single-Dose Study Comparing the Biosimilarity of HOT-1010 With Bevacizumab (Avastin®) in Chinese Healthy Male Subjects

Abstract: Objective: This study was conducted to compare the pharmacokinetics, safety and immunogenicity of HOT-1010 with bevacizumab (Avastin®) in Chinese healthy male subjects.Methods: A single-center, randomized, double-blind, single-dose, parallel trial was performed in 84 Chinese healthy male subjects who randomly (1:1) received a single intravenous infusion of 1 mg/kg HOT-1010 or Avastin® for 90 min and followed up for 85 days. Serum concentrations of bevacizumab were analyzed by enzyme-linked immunosorbent assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The mean t 1/2 (15 days) for STC510 was similar to that of the reference product, which was consistent with the t 1/2 reported in another bevacizumab study in healthy volunteers [ 22 24 ]. According to reports, this antibody has a small inter-CV among Chinese patients, but a large volume of distribution and a 14- to 16-day half-life [ 25 28 ]. A similar pattern of elimination for STC510 was also observed in this study, beginning with a rapid blood clearance stage lasting about 7 days, and then followed by a gradual clearance phase.…”
Section: Discussionmentioning
confidence: 99%
“…The mean t 1/2 (15 days) for STC510 was similar to that of the reference product, which was consistent with the t 1/2 reported in another bevacizumab study in healthy volunteers [ 22 24 ]. According to reports, this antibody has a small inter-CV among Chinese patients, but a large volume of distribution and a 14- to 16-day half-life [ 25 28 ]. A similar pattern of elimination for STC510 was also observed in this study, beginning with a rapid blood clearance stage lasting about 7 days, and then followed by a gradual clearance phase.…”
Section: Discussionmentioning
confidence: 99%
“…Second, healthy subjects were used in the PK similarity study to ensure the study population's homogeneity and represent the most sensitive population for evaluating the PK similarity, as patients have potentially complicated factors that possibly influence PK profiles, such as disease complications and concomitant medications. 18 Third, as an immunocompetent population, healthy subjects are more suitable for comparing the safety and immunogenicity of biological agents.…”
Section: Discussionmentioning
confidence: 99%
“…The 2‐period, crossover study conducted in healthy male subjects is based on the following design considerations: First, the short half‐life (≈75 hours) and low immunogenicity of rhTNFR:Fc, as well as the smaller sample size, suggested that the crossover study is preferred to a parallel design. Second, healthy subjects were used in the PK similarity study to ensure the study population's homogeneity and represent the most sensitive population for evaluating the PK similarity, as patients have potentially complicated factors that possibly influence PK profiles, such as disease complications and concomitant medications 18 . Third, as an immunocompetent population, healthy subjects are more suitable for comparing the safety and immunogenicity of biological agents.…”
Section: Discussionmentioning
confidence: 99%